Tudi zaposlovanje na črno pomeni segmentacijo trga dela - Končar, Polonca (Delavci in delodajalci, 2013)
The abolishment of labour market segmentation was one of the important objectives of the new ERA and the amendments of the Regulation of the Labour Market Act. The attention has been focused on the fixed-term employment and the older workers. The authoress wants to emphasize that the undeclared work represents the important case of labour market segmentation. The approach of the EU in tacckling undeclared work is described. The paper also examines the activity of ILO in the respective field.The special attention is drawn to the new Convention No. 189 on domestic workers and to the role of te labour inspection in the fight against the undeclared employment.Our legislation on the prevention of the undeclared employment contains a range of preventive measures which are intended to move undeclared employment into the declared one. New forms of work are in question, which do not contribute always to the realisation of the idea that work should be performed as a rule on the basis of the employment contract.
Keywords: delo na črno; delovno pravo; trg dela; trg delovne sile